Pengaruh Bauran Pemasaran terhadap Motivasi Pembelian Konsumen pada Produk Yakult di Kota Padang - Sarianti, Rini; Atris, Oleh (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2013)
This research background overshadow by challenge faced by Yakult Indonesia, In where Indonesian people generally not yet accustomed to drink prebiotic drink, while other Asian have accustomed to drink prebiotic drink. Therefore, Producer of Yakult try to grow the habit to consume of Yakult and to give motivate by using marketing stimulus (Marketing Mix) to the consumer. This research aim to analyze: 1) Which marketing mix variable (product, price, distribution or promotion) what most is influencing the purchasing motivation of Yakult product by consumer in Padang City. 2) Toward impact of product to purchasing motivation of Yakult product by consumer in Padang City. 3) Toward impact of price to purchasing motivation of Yakult product by consumer in Padang City. 4) Toward impact of promotion to purchasing motivation of Yakult product by consumer in Padang City. 5) Toward impact of distribution to purchasing motivation of Yakult product by consumer in Padang City. Type of this research is causative research. As the result variable of product and variable of price do not significant influence purchasing motivation, variable of promotion and variable of distribution owning influence to purchasing motivation of consumer atÂ Yakult productÂ inÂ Padang City. Suggestion to company, promotion and distribution need remain to be improved to utilize to maintain and draw many consumers. Company also have to strengthen product utilize creator motivate purchasing to consumer. And also pricing has to carefully.